Upaya pemeliharaan dan peningkatan mutu kayu sengon dengan bahan anti oksidan dan pemutih - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
The white colour wood such as sengon or fresh lumber often discoloured by fungi and chemical process. An effort to prevent wood quality deterioration is treatment using antioxidants and bleach materials. The objective of this research is to know the effect of antioxidants, bleach and wood position on physical & mechanical properties of sengon. Materials used in this research was Sengon wood with dimension 30 cm x 6 cm x 2 cm and chemical materials which consisted of oxalic acid, benzal conium chloride, ammonium phosphate, hydrogen peroxide, sodium hypochlorite with concentration 5%, 7,5% and 10%. The treatment was soaking in five chemical solution for one hour. This research was arranged in factorial experiment in CRD.. Parameter of this research were white ness degree, fuzzy grain, compression.parallel to grain, compression perpendicular to grain and wood hardness. LSD test will be done if there was significant different among source variation. The results of the research showed that soaking with sodium hypochlorite 10% produced higher white ness degree at 52,02% (sapwood) and 50,90% (heartwood). The lowest fuzzy grain degree produced from soaking with benzal conium chloride 5% was 8,08% (sapwood) Compresssion parallel to grain and perpendicular to grain produced from soaking in hypochlorite 10% were. 237 kg/cm2